Procedure proposal for the supplier selection of productive equipment maintenance activities in the sugar mills - Alfonso Llanes, Aramis; Granela Martín, Hugo; Hernández Pascual, Kely; Sánchez Amador, Dorgis (Centro Azúcar Journal, 2008)
To reach an appropriate maintenance of the sugar factories while being repaired is one of the elements that certifies the achievement of an effective operation of the productive equipment during the mill phase; it is for it that the selection of the appropriate suppliers for the benefit of the services of this type that decide to hire becomes an important factor for the enterprise. In work a procedure starting from the Critical Factors of Success of the activity of Maintenance (CFSM) is exposed, it allows to develop this selection of suppliers. It guarantees that the hired supplying enterprises are appropriate to the strategies and maintenance of the factory.